2005
DOI: 10.1002/tea.20062
|View full text |Cite
|
Sign up to set email alerts
|

Promoting fourth graders' conceptual change of their understanding of electric current via multiple analogies

Abstract: For the past two decades, a growing amount of research has shown that the use of analogies in science teaching and learning promotes meaningful understanding of complex scientific concepts This article presents a study in which multiple analogies were used as scaffolding to link students' prior understanding of daily life events to knowledge of the scientific domain. The study was designed to investigate how multiple analogies influence student learning of a complex scientific concept: the electric circuit. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 46 publications
7
78
1
12
Order By: Relevance
“…The explanations offered above are very similar to those reported (Chiu & Lin, 2005: Taiwan 9-10; Tsai et al, 2007: Taiwan 12-17) amongst secondary school students who believe in an attenuation model.…”
Section: Overall Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The explanations offered above are very similar to those reported (Chiu & Lin, 2005: Taiwan 9-10; Tsai et al, 2007: Taiwan 12-17) amongst secondary school students who believe in an attenuation model.…”
Section: Overall Resultssupporting
confidence: 82%
“…This so called "sequence model", is closely aligned to the attenuation model (Chiu & Lin, 2005;Shipstone, 1984;Tsai et al, 2007), and has also been reported by Paatz et al (2004: Germany 16) who found that even more academically able participants are likely to develop and/or have retained this misconception post instruction.…”
Section: The Questionssupporting
confidence: 71%
See 1 more Smart Citation
“…Predominant types of students' conceptions of simple and series electric circuits include unipolar, clashing-currents, crossing-currents, attenuation, sharing, and scientific models (Chiu & Lin, 2005). Students who lack understanding of a complete path for current flow hold a unipolar model that assumes the electric currents flow from one terminal of the battery into the bulb.…”
Section: Students' and Teachers' Understanding About Electric Circuitsmentioning
confidence: 99%
“…The use of analogies for instruction, whether initiated by the text, by the teacher, or by the students themselves, has been shown to improve conceptual learning in a variety of science contexts (Dagher, 1995a;Duit, 1991), including psychology (Mayo, 2001), mathematics (Didierjean & Cauzinille-Marmeche, 1998), biology (Baker & Lawson, 2001;Glynn & Takahashi, 1998;Kaufman, Patel, & Magder, 1996;Mason, 1994;Newby, Ertmer, & Stepich, 1995;Pittman, 1999;Swain, 2000), and physics (Chiu & Lin, 2005;Clement, 1988Clement, , 1989Clement, , 1993Clement, , 1998Heywood & Parker, 1997;Mason & Sorzio, 1996;Stavy, 1991;Wong, 1993aWong, , 1993b. In addition, instructional activities involving student-generated analogies may reveal student understanding better than traditional assessment (Pittman, 1999).…”
Section: Research On Analogiesmentioning
confidence: 99%